Pengaruh Financial Influencer, Literasi Keuangan dan Self-Control Terhadap Keputusan Investasi Masyarakat Aceh Barat - Saparil Saparil; Abu Hassan Makmun; Tio Devilishanti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of Financial Influencers, Financial Literacy, and Self-Control on Investment Decisions among the people of West Aceh. The rapid growth of digital technology has encouraged individuals to access financial information through social media, where Financial Influencers play a major role in shaping investment behavior. This research uses a quantitative method with questionnaires distributed to 100 respondents who have engaged in investment activities. Data were analyzed using validity, reliability, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²) with SPSS version 25. The results show that Financial Influencers have a significant effect on investment decisions. Financial Literacy also has a positive and significant influence, meaning that higher financial knowledge leads to better investment decisions. Self-Control significantly affects investment decisions, indicating that self- regulation is crucial in making rational financial choices. Simultaneously, all three variables have a positive and significant effect on investment decisions. This study concludes that improving financial literacy, self-control, and the wise use of social media can foster smart and sustainable investment behavior in West Aceh.